Epidemiological, clinical and genetic aspects of adult onset isolated focal dystonia in Ireland. (19th September 2016) - Williams, L.; McGovern, E.; Kimmich, O.; Molloy, A.; Beiser, I.; Butler, J. S.; Molloy, F.; Logan, P.; Healy, D. G.; Lynch, T.; Walsh, R.; Cassidy, L.; et al.
Abstract : Background: Adult onset idiopathic isolated focal dystonia presents with a number of phenotypes. Reported prevalence rates vary considerably; well‐characterized cohorts are important to our understanding of this disorder. Aim: To perform a nationwide epidemiological study of adult onset idiopathic isolated focal dystonia in the Republic of Ireland. Methods: Patients with adult onset idiopathic isolated focal dystonia were recruited from multiple sources. Diagnosis was based on assessment by a neurologist with an expertise in movement disorders. When consent was obtained, a number of clinical features including family history were assessed. Results: On the prevalence date there were 592 individuals in Ireland with adult onset idiopathic isolated focal dystonia, a point prevalence of 17.8 per 100 000 (95% confidence interval 16.4−19.2). Phenotype numbers were cervical dystonia 410 (69.2%), blepharospasm 102 (17.2%), focal hand dystonia 39 (6.6%), spasmodic dysphonia 18 (3.0%), musician's dystonia 17 (2.9%) and oromandibular dystonia six (1.0%). Sixty‐two (16.5%) of 375 consenting index cases had a relative with clinically confirmed adult onset idiopathic isolated focal dystonia (18 multiplex and 24 duplex families). Marked variations in the proportions of patients with tremor, segmental spread, sensory tricks, pain and psychiatric symptoms by phenotype were documented. Conclusions: The prevalence of adult onset idiopathic isolated focal dystonia in Ireland is higher than that recorded in many similar service‐based epidemiological studies but is still likely to be an underestimate. The low proportion of individuals with blepharospasm may reflect reduced environmental exposure to sunlight in Ireland. This study will serve as a resource for international comparative studies of environmental and genetic factors in the pathogenesis of the disorder.